Comparison of Zn, Cu, and Fe Content in Hair and Serum in Alopecia Areata Patients with Normal Group - Ladan Dastgheib; Zohreh Mostafavi-pour; Ahmad Adnan Abdorazagh; Zahra Khoshdel; Maryam Sadat Sadati; Iman Ahrari; Sajjad Ahrari; Mahsa Ghavipisheh (Hindawi Limited, 2014)
Background. Alopecia areata (AA) is an autoimmune condition, in which hair is lost from some areas of the body. Though its etiopathogenesis is not fully understood, there are claims that imbalance of trace elements may trigger the onset of AA, by distorting immune functions. In this study, we tried to investigate the relationship between AA and iron, zinc, and copper levels of serum and hair. Materials and Methods. Sixteen female patients with AA (14-40 years old) and 27 healthy female controls were enrolled in this study. Serum and hair level of iron, zinc, and copper were measured by flame emission spectroscopy. The resulting data was analyzed with SPSS15. Results. We did not detect a significant difference in the serum and hair level of iron, zinc, and copper between patients and controls. There was a significant correlation between serum and hair level of iron (r=0.504,  P=0.001), zinc (r=0.684,  P=0.0001), and copper (r=0.759, P=0.0001) in patients and controls. Discussion and Conclusion. According to this study, there was no statistically significant difference between trace elements among AA patients and controls. So the trace elements level in hair and serum may not be relevant to the immunologic dysfunction that exists in AA patients.